Study on the Anti-Adenovirus Mechanism of Sargassum fusiforme - Feng, Guanrong; Zhang, Duo; Peng, Chengcheng; Wu, Mingjiang; Xiao, Pengpeng; Li, Nan (Frontiers in Cellular and Infection Microbiology, 2022)
Human adenovirus (HAdV) has a worldwide distribution and remains a major pathogen that leads to infections of the respiratory tract. No specific treatments or vaccines are yet available for HAdV infection. Sargassum fusiforme, an edible seaweed, has attracted a lot of attention for its various bioactivities. S. fusiforme has been reported to exhibit antiviral activity. However, research studies about its anti-HAdV activity are few. In this research, we found that S. fusiforme had low cytotoxicity and possessed anti-human adenovirus type 7 (HAdV7) activity in vitro, and the most effective ingredient was alginate. The time of addition assay demonstrated inhibitory effects that were observed in all life stages of the virus. In addition, we observed that the antiviral activity of alginate against HAdV7 infection might be closely related to the endoplasmic reticulum stress (ERS) pathway. Taken together, these results suggest that S. fusiforme extracts have potential application in the prevention and treatment of HAdV infection.